konstruktivisme dengan kemampuan berpikir kritis - Nasution, Sofyan husein (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2024)
The aim of this research is to identify the influence and implementation of the constructivist approach on students' critical thinking abilities. This research technique is based on Systematic Literature Review (SLR), which examines in more depth the topics and problems that have been prepared using various previous research sources that are in line with the topic being discussed. The previous research collected was accredited by Sinta, Scopus, Google Scholar, DOAJ. The publication of the data obtained is from the last 10 years and concerns the topics, namely: Definition of constructivism, social constructivism approach, influence of constructivism in the learning environment, constructivism approach to students' critical thinking abilities. Constructivism is an individual's view of developing an idea or his own ideas in analyzing something new through experience and what he learns. There is the influence of the constructivist approach in increasing the learning activities of college level students, especially for mathematics. Independent learning can have an influence on students' skills in critical thinking, this is because it is able to give students freedom to find references about learning topics through various sources of data or information in the absence of a helping hand or help from other individuals.